Access to PCNA by Srs2 and Elg1 Controls the Choice between Alternative Repair Pathways in Saccharomyces cerevisiae - Arbel, Matan (mBio, 2020)
During DNA replication, stalling can occur when the replicative DNA polymerases encounter lesions or hard-to replicate regions. Under these circumstances, the processivity factor PCNA gets ubiquitylated at lysine 164, inducing the DNA damage tolerance (DDT) mechanisms that can bypass lesions encountered during DNA replication. PCNA can also be SUMOylated at the same residue or at lysine 127. Surprisingly, pol30-K164R mutants display a higher degree of sensitivity to DNA-damaging agents than pol30-KK127,164RR strains, unable to modify any of the lysines. Here, we show that in addition to translesion synthesis and strand-transfer DDT mechanisms, an alternative repair mechanism (“salvage recombination”) that copies information from the sister chromatid is repressed by the recruitment of Srs2 to SUMOylated PCNA. Overexpression of Elg1, the PCNA unloader, or of the recombination protein Rad52 allows its activation. We dissect the genetic requirements for this pathway, as well as the interactions between Srs2 and Elg1.